Trading in the Presence of Short-Lived Private Information: Evidence from Analyst Recommendation Changes. (6th August 2018) - Kadan, Ohad; Michaely, Roni; Moulton, Pamela C.
Abstract : We use a proprietary data set to test the implications of several asymmetric information models on how short-lived private information affects trading strategies and liquidity provision. Our identification rests on information acquisition before analyst recommendations are publicly announced. We provide the first empirical evidence supporting theoretical predictions that early-informed traders "sell the news" after "buying the rumor." Further, we find distinct profit-taking patterns across different classes of institutions. Uninformed institutions, but not individuals, emerge as de facto liquidity providers to better-informed institutions. Placebo tests confirm that these trading patterns are unique to situations in which some investors have a short-lived informational advantage.